Asymptotic Stability and Asymptotic Synchronization of Memristive Regulatory-Type Networks - Jin-E Zhang (Advances in Mathematical Physics, 2017)
Memristive regulatory-type networks are recently emerging as a potential successor to traditional complementary resistive switch models. Qualitative analysis is useful in designing and synthesizing memristive regulatory-type networks. In this paper, we propose several succinct criteria to ensure global asymptotic stability and global asymptotic synchronization for a general class of memristive regulatory-type networks. The experimental simulations also show the performance of theoretical results.